Prospective of nanoscale metal organic frameworks [NMOFs] for cancer therapy. (February 2021) - Shait Mohammed, Mohammed Razeeth; Ahmad, Varish; Ahmad, Abrar; Tabrez, Shams; Choudhry, Hani; Zamzami, Mazin A.; Bakhrebah, Muhammed A.; Ahmad, Aftab; Wasi, Samina; Mukhtar, Hasan; Khan, Mohammad Imran
Highlights: NMOFs are complex crystalline materials with excellent surface properties for drug designing and delivery. The imaging and therapeutic potentialities of NMOFs for cancer is currently hot topics in academic and industrial research. In-vivo and in-vitro biocopatability and toxicity of both NMOFs and MOFs are explored in many respects. There is more need for understanding both NMOFs and MOFs mechanism of action and pharmacokinetics. Abstract: Nano metal organic frameworks (NMOFs) belong to the group of nanoporous materials. Over the decades, the conducted researches explored the area for the potential applications of NMOFs in areas like biomedical, chemical engineering and materials science. Recently, NMOFs have been explored for their potential use in cancer diagnosis and therapeutics. The excellent physico-chemical features of NMOFs also make them a potential candiadate to facilitate drug design, delivery and storage against cancer cells. In this review, we have explored the characterstic features, synthesis methods, NMOFs based drug delivery, diagnosis and imaging in various cancer types. In addition to this, we have also pondered on the stability and toxicological concerns of NMOFs. Despite, a significant research has been done for the potential use of NMOFs in cancer diagonostic and therapeutics, more information regarding the stability, in-vivo clearance, toxicology, and pharmacokinetics is still needed to ehnace the use of NMOFs in cancer diagonostic and therapeutics.